Anteseden Dan Konsekuensi Dari Keterlibatan Kerja Serta Dampaknya Terhadap Kinerja - C. Catur Widayati; Agus Arijanto; Purnamawati Hellen Widjaja; Yenita (Jurnal Ekonomi, 2023)
This research aims to determine the influence or relationship between three independent variables, namely Transformational Leadership, Quality of Work Life and Company Reputation on one dependent variable, namely Work Engagement in Employees. Quantitative analysis method using the SEM Smart PLS 3.3 analysis tool. The results of hypothesis testing show that transformational leadership, quality of work life, company reputation have a positive and significant effect on work engagement; Transformational leadership has no effect on employee performance; while company reputation, work engagement and quality of work life have a positive and significant effect on employee performance.